Incidentally Identified Pulmonary AVM: An Unusual Cause for Stroke in a Young Patient - Vinod Kalapurackal Mathai; Dale Sebire; Scarlett Bowen (Case Reports in Neurological Medicine)
Pulmonary arteriovenous malformation is an uncommon though important potential source for embolic right-to-left extracardiac shunt as a cause for both silent and clinically evident stroke. We present this case to highlight this pathology as a cause for stroke, the importance of treating this malformation, even if incidentally identified, and finally the role of echocardiography in screening for extracardiac shunt and indicating those patients that may benefit from further investigations looking for extracardiac shunt.